ANALISIS YURIDIS PENYELESAIAN KREDIT MACET PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK. KANTOR CABANG PONTIANAK - NIM. A1011211265, TAWRA SYAHRI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Banks play an important role as financial institutions that are respected and trusted by the public. Banks are responsible for collecting funds from the public in the form of savings or loans and redistributing them to support economic development. PT Bank Rakyat Indonesia (Persero) Tbk., as one of the largest state-owned banks, provides a variety of savings and loan products. This study aims to analyze the legal resolution of non-performing loans at PT Bank Rakyat Indonesia (Persero) Tbk., Pontianak Branch Office. Non-performing loans present a serious obstacle in banking activities because they can affect the stability and health of a bank. Therefore, resolution efforts must comply with legal provisions to avoid losses for both parties